Postnatal development of the Oviduct in the Japanese Quail (Coturnix Coturnix japonica) - Lucy K M (Department of Anatomy, College of Veterinary and Animal Sciences, 1994)
The structure and postnatal development of the oviduct in quails were investigated using 72 birds aged from day-old to 60 days. The growth, morphology and histology of the oviduct were studied using six birds at each age group.